2018
DOI: 10.2478/avutgs-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Hotspot Analysis of Bucharest’s Urban Heat Island (UHI) Using Modis Data

Abstract: The aim of the study is to find the relationship between the land surface temperature and air temperature and to determine the hot spots in the urban area of Bucharest, the capital of Romania. The analysis was based on images from both moderate-resolution imaging spectroradiometer (MODIS), located on both Terra and Aqua platforms, as well as on data recorded by the four automatic weather stations existing in the endowment of The National Air Quality Monitoring Network, from the summer of 2017. Correlation coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Studies of this scale usually use images of low or ultra-low spatial resolution (more than 1 km per pixel), but with very high temporal resolution (less than an hour between images of the same area). Examples of such systems are MODIS and AVHRR [10]. Despite all the advantages of these systems, the low spatial resolution of images makes them unsuitable for regional studies on a city or agglomeration scale.…”
Section: Methods For Obtaining Satellite Imagesmentioning
confidence: 99%
“…Studies of this scale usually use images of low or ultra-low spatial resolution (more than 1 km per pixel), but with very high temporal resolution (less than an hour between images of the same area). Examples of such systems are MODIS and AVHRR [10]. Despite all the advantages of these systems, the low spatial resolution of images makes them unsuitable for regional studies on a city or agglomeration scale.…”
Section: Methods For Obtaining Satellite Imagesmentioning
confidence: 99%
“…Normalized Difference Vegetation Index (NDVI) is one of the most widely applied vegetation indices and an important descriptor of greenness of the biomes. NDVI is considered as land use land cover indicator to quantitatively explore the relationship between the thermal environment and urban expansion [55,56], and to investigate the greening effect on LST changes [32,35,36].…”
Section: Urban Feature Layers 241 Vegetation and Water Bodies Layers Normalized Difference Vegetation Index (Ndvi)mentioning
confidence: 99%
“…Local statistical methods, such as Getis-Ord Gi* [25], allow the thermal spatial pattern to be analyzed by estimating the value of the feature within its spatial context of neighboring features [26]. This latter is a performant and robust method of hot-spot detection already used in previous studies [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown significantly higher UHI in new urban areas compared to old urban areas [31,43], which has been explained by the greater presence of many large industrial agglomerations (major anthropogenic heat sources) in new urban areas [44][45][46]. On the other hand, some other studies have shown the opposite, with higher UHI intensity in old urban areas [41,47], since old urban areas, being the center of commercial and human activities [48,49], have a higher density of impervious surfaces and lower vegetation coverage [35,50,51]. Apparently, one major weakness of these studies is the vague and nonstandard use of new vs. old urban areas, which can greatly affect the results [31,52].…”
Section: Introductionmentioning
confidence: 99%